Comment on: "Cell therapy for heart disease: Trial sequential analyses of two cochrane reviews". Issue 1 (29th December 2016) - Castellini, G; Nielsen, EE; Gluud, C
Abstract : Trial Sequential Analysis (TSA) is a frequentist method to help researchers control the risks of random errors in meta‐analyses. 1 Fisher et al . 2 used TSA on cell therapy for heart diseases. The present article discusses the usefulness of TSA and its dependence on the choice of the parameters for calculation of the required information size and the adjacent monitoring boundaries, and comments on the approach by Fisher et al . 2